平流層驟暖期間大氣潮汐與行星波驅動電離層之變異 - 林佳廷; Lin, Jia-Ting (2021)
位於中低層大氣的大尺度的劇烈天氣事件，特別是發生在冬天極區的平流層驟暖（Sudden Stratospheric Warmings, SSW）事件，是在大氣學界中被廣泛認為研究低層大氣與電離層垂直耦合的絕佳機會，極區平流層SSW事件影響電離層的範圍不僅是在垂直高度上，也包含極區到赤道的緯度範圍延伸，為何極區的SSW影響最劇烈地區的是位於低緯度的電離層？透過觀測與模式研究究竟哪些透過那些物理與化學機制和過程，將地球大氣層的不同區域連結在一起，一直以來是大氣學界之重要課題。早期的研究表明，低緯度電離層對於SSWs所引起的異常相當顯著且持久。在這篇論文中，首先我們對全球電離層分析場(Global Ionospheric Specification, GIS)進行潮汐分解後發現，於2009年SSW事件中，其典型的半日 (12小時) 週期的電離層異常是由太陽和月球半日遷移潮汐 (solar and lunar semi-diurnal migrating tides, SW2與M2) 的疊加作用引起的。造成其半日變化呈現一個大週期振盪 (15天) 是SW2和M2之間拍頻的結果，且M2是造成SSW事件中觀測到的半日變化會隨天數延後現象的主要因子，這表明在SSW事件期間，月球半日遷移潮汐增強所扮演的重要性。 然而SSWs通常只發生在北半球，卻於2019年9月南極地區發生了罕見且增溫幅度創歷史紀錄的SSW，提供了研究南極SSW與電離層耦合提供了絕佳機會，這非常少被探索，因在氣象50年的歷史上，僅發生過三次南極SSW事件。同樣透過分析GIS的結果，我們首次發現於SSW事件中電離層中準六天振盪 (Quasi-6-day Oscillation, Q6DO) 隨時間演化和垂直結構的特徵，是由於SSW改變中氣層和低熱氣層平均風場，達成斜壓不穩定條件產生異常大振幅的準六天波 (Quasi-6-day wave, Q6DW) 所造成的。我們的結果表明，在電離層中觀測到的Q6DO特徵與過去研究的Q6DO氣候特徵在時間和空間上有很大不同，指出由南極SSW驅動之電離層變異的耦合機制復雜，極可能與SW2非線性交互作用產生的次生波有關。 最後，由於過去研究發現在中氣層與低熱氣層中的SW2在SSW事件中在振幅 (兩倍) 與相位 (提前2小時) 上有顯著的改變，故我們利用美國國家大氣研究中心所發展的電離層與大氣耦合模式(NCAR TIE-GCM)模擬，研究其電離層對於模式下邊界條件之SW2大氣潮汐的反應，透過四種不同SW2振幅與相位的組態，探討其對於大氣風場、電離層電漿密度、電動力過程及中性組成影響。其結果指出電離層對於SW2相位的提前，能夠產生符合早上電子密度增加與下午電子密度減少的典型半日變化之SSW電離層效應的特徵，但改變量與觀測有段差距，其機制是透過改變白天E層的電動力過程產生的半天變化的垂直電漿飄移，且達穩定態的時間非常短 (一天)。 另一方面對於增強SW2振幅的模擬實驗結果顯示，僅增強SW2振幅並無法重現典型的SSW電離層效應，而是造成電子密度早上傍晚減少中午增加的現象，且隨模擬時間一長，潮汐消散作用反而造成全面性的電子密度下降。然而當將SW2的振幅增強與相位提前兩者同時改變時，其造成的結果最為符合典型SSW電離層效應，在電漿飄移速度變化的大小也較為接近觀測。除此之外我們也發現在增強SW2振幅的實驗中，白天E層電動力過程對於SW2反應時間尺度起初較快 (數天)，與SW2潮汐風振幅達穩定時間尺度一致，而潮汐消散作用對平均風場向西加速的反應達平衡所需的時間較長 (約一周)，其較為緩慢變化的平均風場又能繼續透過F層電動力過程反饋至電漿飄移，抵銷部分白天來自E層的貢獻。這些結果使我們更好地了解造成電離層變化的原因，尤其是低層大氣中的大尺度太陽熱力和月球引力所誘發的潮汐以及行星波向上傳播的作用。 Large‐scale meteorological disturbances like sudden stratospheric warmings (SSWs) are often of interest for the investigation of a variety of mechanisms and processes that link different regions of the Earth's atmosphere across a wide range of altitudes and latitudes. Earlier studies have shown large and long‐lasting anomalies caused by SSWs in the Earth's daytime ionosphere. In this study, we show that the typical semi-diurnal (12-hrs) ionospheric responses in connection with SSWs are caused by the combined effect of solar and lunar semi-diurnal migrating tides during the 2009 SSW. The 15-day oscillation of the semi-diurnal variations is indeed a result from the beating between solar and lunar semi-diurnal migrating tides. In addition, our results indicate that the observed semi-diurnal variations in ionosphere that progressed toward later local time during the SSW are primarily attributed to the lunar semi-diurnal migrating tides, suggesting the importance of strong enhancements in the lunar semi-diurnal migrating tide during SSWs. These results improve our understanding of the reasons for day‐to‐day variations in the ionosphere and the role of upward propagation of solar and gravitational lunar induced tides from lower altitudes during large-scale meteorological disturbances. However, the SSW usually occurs in the northern hemisphere. In September 2019, a rare and record-breaking SSW occurred in the Antarctic region, providing an opportunity to investigate the ionospheric variabilities connected to the Antarctic SSW, which is seldom explored. We present observations of the time evolution and vertical structure of Quasi-6-Day Oscillation (Q6DO) in the ionosphere generated from the unusually large Quasi-6-day Wave (Q6DW) in the mesosphere and lower thermosphere. Our results show that the observed Q6DO behavior in the ionosphere is quite different from climatological characteristics in the local time and vertical structure, which indicates that the coupling mechanisms driving the ionospheric variability are complicated due to the presence of Antarctic SSW. The two child waves produced by the non-linear interaction between the Q6DW and SW2 could be the possible candidates for the abnormal feature. Finally, we performed TIE-GCM simulations with four different SW2 configurations (in amplitude and phase, respectively) to evaluate their influences on atmospheric wind field, ionospheric plasma density, electrodynamic process, and neutral composition. The results indicate that the ionosphere responds to the electrodynamic process by the tidal variability of SW2 in E-region with a relatively short time scale (three days), while the impact of increasing tidal dissipation on the zonal mean wind takes a longer time scale (about a week), and the slow change in the zonal mean wind field can continue to be fed back to the electrodynamic process through F-region dynamo. Overall, these results enable us to better understand the mechanisms for the changes in the ionosphere, especially the ionospheric responses to the upward propagation of large-scale solar, lunar tides, and planetary waves.